Spatial Analysis of the Variables Involved in the Frequency and Severity of Traffic Accidents on Rural Highways in Pernambuco - Macedo, Márcia; Maia , Maria; Rabbani , Emilia Kohlman; Marinho, Manoel (American Scientific Research Journal for Engineering, Technology, and Sciences, 2021)
Traffic safety depends on a lot of factors associated with traffic accidents and where it takes place. Analyzing how variables related to traffic accidents influences on its frequency and severity may help on the proposition of significant improvement to the effective reduction of said accidents. The goal of this research is to analyze the impact of contributing factors to traffic accidents of any kind, reducing the number of variables related to the statistic model, adjusting it to the brazilian reallity. The methodology was applied in a case study in a 255km patch of a simple lane countryside highway in the state of Pernambuco. Statistics trials were taken to quantify its possible effects on the frequency and severity of traffic accidents. The analysis showed significant factors that contribute to the frequency and severity of the observed accidents. These factors were the amount of traffic (VDMA), radius of the horizontal curve, greide, age range and day of the week. Even though most of the accidents happened in tangent patches, the most severe accidents take place in turns. It also shows that young people between 18 and 30 years old are 22,7% more likely to get involved in fatal accidents than adults over 50 years old, and that in the weekends the chances of an accident occuring is 67% higher than during a week day. The analysis may be used to provide information on future reviews of parameter selection guidelines, especially regarding turns, based on the main parameters of the highway design to reduce risk of accidents in turns.